Concentrationary art : Jean Cayrol, the Lazarean, and the everyday in post-war film, literature, music, and the visual arts /: Jean Cayrol, the Lazarean, and the everyday in post-war film, literature, music, and the visual arts. (2019) - Unknown
No abstract available